Analisis Ketimpangan antar Wilayah di 35 Kabupaten/Kota di Provinsi Jawa Tengah dan Faktor-Faktor yang Mempengaruhinya - Yerikha Christi Gratia; Nugroho SBM (Diponegoro Journal of Economics, 2020)
Indonesia has thousands of islands that is separated by ocean and strait that make one island with another island have different characteristics both in terms of social, economic and cultura. Each region has a different natural potential and quality of resources, causing regional disparity. This study aims to determine the impact of fiscal decentralization, direct expenditure, indirect expenditure, inflation, and labor on regional disparity in 35 districts/cities in Central Java Province from 2011 to 2017. This study uses secondary data obtained from the Agency Central Statistics of Central Java Province, Director General of Fiscal Balance and World Bank. This research uses panel data method which consists of 35 regencies / cities in Central Java Province for 7 years. From the analysis it is known that the variable degree of fiscal decentralization, direct expenditure, indirect expenditure, inflation, and labor affect the inequality between regions in 35 districts / cities in Central Java Province. With 5% degree of relience. Fiscal decentralization, direct expenditure and labor have a positive influence on regional disparity in 35 districts / cities in Central Java Province, while indirect spending and inflation have a negative effect on regional disparity in 35 districts / cities in Central Java Province.